2017
DOI: 10.1128/mbio.01903-17
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Distributions and Temporal Variability in the Ocean’s Interior

Abstract: Bacteriophages are numerically the most abundant DNA-containing entities in the oligotrophic ocean, yet how specific phage populations vary over time and space remains to be fully explored. Here, we conducted a metagenomic time-series survey of double-stranded DNA phages throughout the water column in the North Pacific Subtropical Gyre, encompassing 1.5 years from depths of 25 to 1,000 m. Viral gene sequences were identified in assembled metagenomic samples, yielding an estimated 172,385 different viral gene f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 65 publications
11
92
1
Order By: Relevance
“…4). The depthstratified viral community is analogous to that reported from ocean (Hurwitz et al, 2015;Mizuno et al, 2016;Paez-Espino et al, 2016;López-Pérez et al, 2017;Luo et al, 2017) and likely reflects the depth-stratified community of bacterioplankton (Okazaki and Nakano, 2016) (Table S4). The viral community was generally stable in the hypolimnion (the Bray-Curtis dissimilarity of the communities between consecutive months = 0.21-0.34; except for September to October and December to January as discussed later) compared to the epilimnetic community (0.54-0.68) (Figs.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…4). The depthstratified viral community is analogous to that reported from ocean (Hurwitz et al, 2015;Mizuno et al, 2016;Paez-Espino et al, 2016;López-Pérez et al, 2017;Luo et al, 2017) and likely reflects the depth-stratified community of bacterioplankton (Okazaki and Nakano, 2016) (Table S4). The viral community was generally stable in the hypolimnion (the Bray-Curtis dissimilarity of the communities between consecutive months = 0.21-0.34; except for September to October and December to January as discussed later) compared to the epilimnetic community (0.54-0.68) (Figs.…”
supporting
confidence: 64%
“…Since no integrase gene was found in their genomes, they may have existed in a host's cell in an extrachromosomal or pseudolysogenic manner. As proposed for the deep ocean (Weinbauer et al, 2003;Paul, 2008;Mizuno et al, 2016;Luo et al, 2017), the lysogenic strategy in deeper water likely results from low bacterioplankton productivity, which is insufficient to support lytic viral propagation. Lytic induction can be triggered by environmental stressors such as pH, temperature, nutrients, oxidative stress, and solar radiation (Weinbauer, 2004;Howard-Varona et al, 2017).…”
Section: Spatiotemporal Dynamics Of the Viral Communitymentioning
confidence: 99%
“…). The depth‐stratified viral community is analogous to that reported from ocean (Hurwitz et al ., ; Mizuno et al ., ; Paez‐Espino et al ., ; López‐Pérez et al ., ; Luo et al ., ) and likely reflects the depth‐stratified community of bacterioplankton (Okazaki and Nakano, ) (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…As no integrase gene was found in their genomes, they may have existed in a host's cell in an extrachromosomal or pseudolysogenic manner. As proposed for the deep ocean (Weinbauer et al ., ; Paul, ; Mizuno et al ., ; Luo et al ., ), the lysogenic strategy in deeper water likely results from low bacterioplankton productivity, which is insufficient to support lytic viral propagation. Lytic induction can be triggered by environmental stressors such as pH, temperature, nutrients, oxidative stress and solar radiation (Weinbauer, ; Howard‐Varona et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…More than a decade ago, studies of marine, hydrothermal, and soil environments suggested that lysogeny could be more prevalent than assumed based on culture-based analysis of virus-microbe interactions [15][16][17][18]. This evidence has been augmented by recent studies identifying viral dark matter -including integrated and extrachromosomal viral sequences -in microbial genomes [19][20][21]. Yet, despite increasing evidence of the relevance of persistent infections in situ the ecological study of phage has not integrated a common metric to compare the contextdependent fitness of lytic, temperate, and other chronic viral strategies.…”
mentioning
confidence: 99%